(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2022)
A study was conducted at Babugonj upazilla under the district of Barishal in Bangladesh during the period from 1st December, 2020 to 29th April, 2021. To determine the prevalence and therapeutic efficiency of Peste des Petits Ruminants in goat. A total number of 523 diseases cases were recorded randomly irrespective of age ,sex ,and breed over the study period, among them 118 case were clinically diagnosed as Peste des Petits Ruminants. The overall prevalence of Peste des Petits Ruminants in goat was 22.56%. Diarrhoea, dyspnea, oculonasal discharge, rough hair coat, dullness, depression, and erosion on the lip were the common findings during clinical examination of Peste des Petits Ruminants patients. The prevalence of Peste des Petits Ruminants in different age group upto 4 month, 5-8 month,9-12 month, Above 12 month were 11.02%, 31.36%, 33.90% and. 23.73% respectively. Female are more susceptible (76.27%) than male (23.72%). Black bengal goats were more susceptible (69.49%) than Jamunapari (30.50%). Peste des Petits Ruminants causes higher mortality and heavy economic losses in every year which may be reduced substantially by proper vaccination and other manage mental approaches. Asian Australas. J. Biosci. Biotechnol. 2021, 6 (3), 142-146